Who is publishing in ecology and evolution? the underrepresentation of women and the Global South - Hughes, Alice C.; Than, Kay Zin; Tanalgo, Krizler C.; Agung, Ade Prasetyo; Alexander, Tendu; Kane, Yakhouba; Bhadra, Sreetama; Chornelia, Ada; Sritongchuay, Tuanjit; Simla, Pattraporn; Chen, Yanhua; Chen, Xing; et al. (Frontiers in Environmental Science, 2023)
Most global biodiversity is in developing economies. Decades of capacity building should have built sufficient in-country capacity to develop biodiversity baselines; yet has effort provided the expertise to build these baselines? Grants and access to research opportunities are often linked to success in publishing, with the H-index providing the main metric of academic success. Recent compilations of 'Top Researchers in Ecology and Evolution' included 5419 researchers. However, over half are from just three countries (USA, UK and Australia), and 83% come from 12 higher-income countries. Even in lower-income economies the majority of the few “high impact” researchers are originally from higher-income economies. Only China had a high proportion of their high-impact non-Caucasian researchers, with the majority of researchers coming from that region. Women were also underrepresented across the globe, only three countries had more than 20% of top-performing ecologists being female. Ultimately, despite decades of capacity building, we are still failing to build in-country capacity for research or to provide sufficient support for female ecologists to publish and lead the field. Here we discuss why these issues persist, and how we might improve representation and access to opportunity and support for all groups, and provide the analysis needed to provide solutions to global challenges in biodiversity conservation, which require diverse representation to develop effective, and nuanced solutions.